(untitled) (Research, Society and Development, 2019)
The teaching-learning process should be based on cognitive psychology, with motivational methodologies that activate mental functions in the student and provide the teacher to lead the teaching process in a problematizing way. In this perspective the present this article proposes to analyze the learning process of the Problem Situation Activity in Spatial Geometry performed through a board game; based on the theory of stage formation of mental actions of Galperin and the problematic teaching of Majmutov; in the second year students of higher technical education in Agronomy of the Agro technical School of the Federal University of Roraima. The research uses qualitative and quantitative data, but the main focus is qualitative. The data collection instruments used was written tests and interaction with the game. The methodological procedures of the investigation are divided into four stages: i) diagnosis, iii) planning, iii) execution and iv) feedback and correction. Before the analysis of the qualitative and quantitative results of the diagnostic, formative and final evaluation, it was concluded that the activities and didactics carried out in the four moments of the research contributed to learning and understanding in the execution of each action performed by the students, considering that the performance of the majority of the students was quite satisfactory and progressive in relation to the mathematical content of Plane and Space Geometry